Enterococcus faecalis endocarditis presenting as meningitis - S. I. Nawaz; S. C. Weerasinghe; U. Ralapanawa; S. Abeyagunawardena; W. A. T. A. Jayalath (Asian Journal of Internal Medicine)
Infective endocarditis is a disease with variable presentations and multi-systemic manifestations. It is associated with life-threatening neurological complications including stroke, meningitis, seizures and cerebral and spinal abscesses which arise due to systemic septic embolisation from the infected heart valves. Neurological complications may be the initial presentation of infective endocarditis. We report a case of a patient who presented with fever, confusion and a cardiac murmur following recent orthopaedic surgery of the hand. Although meningitis was the initial working diagnosis, positive blood cultures, echocardiogram and neuroimaging aided the final diagnosis of Enterococcus faecalis positive infective endocarditis complicated with meningitis and a haemorrhagic cerebral infarct. He was successfully treated with intravenous antibiotics.